Pragmatism and the philosophy of religion - Slater, Michael R., 1976- (Cambridge University Press, 2014)
In this book, Michael Slater provides a new assessment of pragmatist views in the philosophy of religion. Focusing on the tension between naturalist and anti-naturalist versions of pragmatism, he argues that the anti-naturalist religious views of philosophers such as William James and Charles Peirce provide a powerful alternative to the naturalism and secularism of later pragmatists such as John Dewey and Richard Rorty. Slater first examines the writings of the 'classical pragmatists' - James, Peirce, and Dewey - and argues for the relevance of their views for thinking about such topics as the nature of religion and the viability of natural theology. His final three chapters engage with the religious views of later pragmatists such as Rorty and Philip Kitcher, and with current philosophical debates over metaphysical realism, naturalism, and evidentialism. His book will be of particular interest to philosophers of religion, theologians, and specialists in American philosophy.